Catalytic Decomposition of Dichlorodifluoromethane (CFC-12) Over Solid Super Acid MoO3/ZrO2 - LIU, TIANCHENG; NING, PING; WANG, YA-MING; GAO, HONG (Asian Journal of Chemistry, 2010)
Catalytic decomposition of dichlorodifluoromethane (CFC-12) in presence of water vapour and oxygen was studied over a series of solid super acids that have different ZrO2 content using a fixed-bed reactor. CO2 and CClF3 were the main-products and no CO was detected as by-product. The decomposition activity depended on the calcination temperature and the ZrO2 content. Calcined at 450 ºC and 20-40 % ZrO2 content were the best catalyst preparation conditions. Adopting low concentration of oxygen and CFC-12 and high concentration of water vapour is preferable to the achievement of high conversion of CFC-12 and selectivity for CO2. The catalytic activity of MoO3/ZrO2 remained steady for 100 h on stream.